Pengaruh Modernisasi Sistem Administrasi Perpajakan, Pengetahuan Perpajakan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM dengan Sosialisasi Perpajakan Sebagai Pemoderasi - Eka Aulianavisha Hamida; Hasnawati (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to analyze and prove the influence of modernization of the tax administration system, taxpayer knowledge and tax sanctions on MSME taxpayer compliance in DKI Jakarta. This type of research is quantitative using primary data and measured using a Likert scale. The number of samples used in this research was 163 MSME individual taxpayer respondents in DKI Jakarta. This research uses quantitative research methods using the Statistical Package for the Social Sciences (SPSS) program.. The results of this research indicate that the modernization of the tax administration system and tax sanctions have a positive and significant effect on MSME taxpayer compliance, while tax knowledge has no influence and is not significant on MSME taxpayer compliance. Tax Socialization is able to moderate the modernization of the tax administration system towards MSME taxpayer compliance. Tax socialization is unable to moderate tax knowledge and tax sanctions on MSME taxpayer compliance.